The case for combining a large low-band very high frequency transmitter with multiple receiving arrays for geospace research: a geospace radar - Hysell, D. L. (2019)
We argue that combining a high-power, large-aperture radar transmitter with several large-aperture receiving arrays to make a geospace radar—a radar capable of probing near-Earth space from the upper troposphere through to the solar corona—would transform geospace research. We review the emergence of incoherent scatter radar in the 1960s as an agent that unified early, pioneering research in geospace in a common theoretical, experimental, and instrumental framework, and we suggest that a geospace radar would have a similar effect on future developments in space weather research. We then discuss recent developments in radio-array technology that could be exploited in the development of a geospace radar with new or substantially improved capabilities compared to the radars in use presently. A number of applications for a geospace radar with the new and improved capabilities are reviewed including studies of meteor echoes, mesospheric and stratospheric turbulence, ionospheric flows, plasmaspheric and ionospheric irregularities, and reflection from the solar corona and coronal mass ejections. We conclude with a summary of technical requirements.